(untitled) (Journal of Parents and Teachers, 2026)
For younger children, going back to school is a matter of routine, because deep down, every new school year is pretty much the same. However, there is a big leap from primary school to secondary school, and everything changes. That is why we are offering a short guide to help students cope with this new beginning, as well as some tips to make this stage a success.